Leverage and its impact on earnings and share price a special reference to listed companies of colombo stock exchange (cse) in sri lanka - Nimalathasan, B.; Elangkumaran, P. (University of Jaffna, 2013)
This study investigates the impact of leverage on earnings and share price of listed companies on Colombo Stock Exchange (CSE) in Sri Lanka. The study was identified 20 companies listed on the CSE for the period from year 2007/2008 to 2011/2012.The Degree of Operating Leverages (DOL), Degree of Financial Leverage (DFL) & Degree of Combined Leverage (DCL) are the independent variables and Earning Per Share (EPS) and Share Price (SP) are the dependent variables for this study. The present study used the correlation coefficient and linear regression to measure the variables. The findings revealed that only 4% earnings can be explained by DOL, DFL and DCL and there is no significant relationship with EPS. It is also found that 3% SP is attributed by DOL, DFL and DCL and there is no significant relationship with SP. Thus, fixed operating expenses and the financing mix decisions of the firm are not significantly impact the earning capacity of the listed companies in CSE.
Keywords: Leverage; Earnings per share (EPS); Share price (SP)